The international convention on the protection of the rights of all migrant workers and members of their families - Camós Victoria, Ignacio; Rojo Torrecilla, Eduardo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article is an approach to the content of the 1990 International Convention on the Protection of the Rights of All Migrant Workers and Members of their Families, in which the aim is not only to broach the content of this important international legislative instrument, but also to highlight its axes, as well as the contribution that this text makes to the recognition of the rights of migrants and the members of their families, particularly with regard to those who are in an irregular situation. The social integration of these persons and the fight against the traffic of immigrants are other axes of the document which clearly declares itself as opposed to establishing barriers against the recognition of basic rights, as these favour clandestine immigration, talking the stand that the administrative situation of those who emigrate should not be an obstacle for the recognition and enjoyment, under equal conditions, of basic human rights.
Keywords: Immigration; International Convention; Human rights; Irregular immigration; Equality of treatment.